2021
DOI: 10.3390/pathogens10040479
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology Analysis of SARS-CoV-2 in Syncytiotrophoblast and Hofbauer Cells in Placenta from a Pregnant Woman and Fetus with COVID-19

Abstract: A small number of neonates delivered to women with SARS-CoV-2 infection have been found to become infected through intrauterine transplacental transmission. These cases are associated with a group of unusual placental pathology abnormalities that include chronic histiocytic intervillositis, syncytiotrophoblast necrosis, and positivity of the syncytiotrophoblast for SARS-CoV-2 antigen or RNA. Hofbauer cells constitute a heterogeneous group of immunologically active macrophages that have been involved in transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 48 publications
1
16
0
4
Order By: Relevance
“…There have been previous individual case reports of both positivity and negativity of Hofbauer cells for SARS-CoV-2 staining, 26,38,63 but this present article describes the first systematic investigation of SARS-CoV-2 involving Hofbauer cells and other cell types in a large cohort of placentas infected with the virus. Evaluation of 22 placentas infected with SARS-CoV-2 revealed that Hofbauer cells were immunohistochemically positive for viral staining in 4 cases (18%) ( Cases 19,15,20,21).…”
Section: Discussionmentioning
confidence: 86%
“…There have been previous individual case reports of both positivity and negativity of Hofbauer cells for SARS-CoV-2 staining, 26,38,63 but this present article describes the first systematic investigation of SARS-CoV-2 involving Hofbauer cells and other cell types in a large cohort of placentas infected with the virus. Evaluation of 22 placentas infected with SARS-CoV-2 revealed that Hofbauer cells were immunohistochemically positive for viral staining in 4 cases (18%) ( Cases 19,15,20,21).…”
Section: Discussionmentioning
confidence: 86%
“…Thorough literature search aimed at including all potentially relevant studies, multitude of histopathological anomalies and the large numbers of included cases 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 represent the main strengths of the present systematic review. The retrospective design of most of the included studies, small sample size, and heterogeneity in histopathological anomalies observed, are the main limitations of this systematic review.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Several reports suggest an increased risk of placental lesions due to hypoperfusion and inflammation in women with SARS-CoV-2 infection. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 The potential association between SARS-CoV-2 and impaired placental function is crucial because it might lead to fetal decompensation and increased risk of perinatal mortality and morbidity. 66 , 67 Despite this, the occurrence of placental histopathological abnormalities in pregnancies complicated by SARS-CoV-2 infection is yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical transmission of corona viruses is reported to be rare 4 . Nevertheless, the likelihood of placental transmission can be supported by presence of angiotensin-converting enzyme 2 and transmembrane serine protease 2 in placental epithelium, which are paramount in cellular infiltration of the SARS CoV-2 3 . A systematic review by Kotlyar AM, et al 4 revealed that there is a 3.2% risk of transmitting the virus by infected mothers in the third trimester as confirmed by nasopharyngeal RT-PCR.…”
Section: Discussionmentioning
confidence: 99%